Plastic surgery of a critical defect in the tracheal wall using a cell engineering design and a stent in an experiment - A. V. Denisova; S. S. Dydykin; E. I. Safronova; N. N. Piskunova; A. A. Panteleyev; E. D. Grigoryevsky; S. I. Kolchenko (Сеченовский вестник, 2019)
Aim. To experimentally test a new method for plastic surgery of a critical defect in the tracheal wall using a cell engineering construction and a stent. Materials and methods. The object of the experiment was 13 Oryctolagus Chinchilla rabbits. To determine the critical size of the tracheal defect, a “Defects Group” (n=11) was created, divided into two subgroups depending on the width of the mucous and submucosal defect, the length of the defect was standard - 15 mm. Subgroup 1 included animals with a defect width of